Counseling Regarding Sexual and Reproductive Behavior: Principles and Practices of Catholic Priests Orientaciones sobre el comportamiento sexual y reproductivo: principios y prácticas de los sacerdotes católicos Orientações sobre o comportamento sexual e reprodutivo: princípios e práticas dos sacerdotes católicos - Luiza Akiko Komura Hoga; Cristiane Alves Tiburcio; Ana Luiza Vilela Borges; Elma Lourdes Campos Pavone Zoboli; Rocio Elizabeth Chavez-Alvarez (Universidade de São Paulo, 2010)
Considering and respecting religious beliefs and values is vital for delivering integral health care. This study describes the religious principles and guidance provided by Catholic priests on sexuality and reproduction. The oral history method was used. Interviews were carried out between August 2007 and May 2008 and were analyzed in an inductive and interpretive manner to acquire a deep focus on the theme. Thirteen Catholic priests from the city of São Paulo, SP, Brazil were interviewed. Counseling provided by the priests has a traditional and conservative character and is based on principles of Catholic doctrine. Health education and promotion activities involving aspects related to sexuality and reproduction should be relevant and permeated with ethical considerations from the perspective of health care services' users, including religious perspectives. La consideración y el respeto por las creencias y valores religiosos son vitales para la integralidad de la asistencia a la salud. El objetivo de este estudio fue describir los principios religiosos y las orientaciones en el ámbito de la sexualidad y reproducción ofrecidas por los sacerdotes católicos. El método de la historia oral fue desarrollado, las entrevistas ocurrieron entre agosto de 2007 y mayo de 2008, fueron analizadas de forma inductiva e interpretativa con un enfoque profundo en el tema. Los entrevistados fueron 13 sacerdotes de la Iglesia Católica de la Ciudad de Sao Paulo. Las orientaciones ofrecidas por los sacerdotes presentan carácter tradicional y conservador y son basadas en principios de la doctrina Católica. Las actividades de educación y promoción de la salud envolviendo aspectos relacionados a la sexualidad y reproducción deben estar impregnadas por la ética, siendo significativas, según la perspectiva de los usuarios de los servicios de salud. A consideração e o respeito às crenças e valores religiosos são vitais para a integralidade da assistência à saúde. O objetivo deste estudo foi descrever os princípios religiosos e as orientações no âmbito da sexualidade e reprodução, fornecidos pelos sacerdotes católicos. O método da história oral foi desenvolvido, e as entrevistas ocorreram entre agosto de 2007 e maio de 2008, analisadas de forma indutiva e interpretativa para o enfoque profundo no tema. Os entrevistados foram 13 sacerdotes da Igreja Católica da cidade de São Paulo. As orientações fornecidas pelos sacerdotes apresentaram caráter tradicional e conservador, pautadas em princípios da Doutrina Católica. As atividades de educação e promoção da saúde, envolvendo aspectos relacionados à sexualidade e reprodução, devem estar permeadas pela ética, sendo significativas, segundo a perspectiva dos usuários dos serviços de saúde.